A development of virtual laboratory as a tool for form four chemistry subject / Nurul Huda Basiran - Basiran, Nurul Huda (2005)
The use of chemistry is to apply the mathematical procedures to the chemical phenomena. One of the major problems in chemistry learning is those students do the calculation that leads to a narrow focus on skills. By using the virtual laboratory, it can help to simulate the chemical phenomena to real world, as scenario based learning. Thus, this project presents a prototype of virtual laboratory to offer experiment virtually through multimedia approach. By using the virtual laboratory, the common tools in lab will be replaced by virtual tools to allow the student do the experiment task step by step by using simulation software.The objectives of this project are to evaluate the effectiveness of virtual laboratory in the performance learning and to develop a virtual laboratory for Form Four Chemistry subject in Particle Theory of Matter part. This project is focus to the desktop virtual laboratory as a teaching tool, explored by keyboard and mouse, with 2D and 3D visualization. The methodology of this research is Development Life Cycle Model to complete the project. In order to evaluate the effectiveness, questionnaire based on content related will be given to two groups of students, incorporating a virtual laboratory group and a real lab experimental group to compare the learning performance of the two groups